1990
DOI: 10.1111/j.1600-079x.1990.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Light‐Induced Decrease of N‐Acetyltransferase Activity in Explanted Chick Pineal Glands

Abstract: The ontogeny of chick pineal serotonin N-acetyltransferase (NAT) activity was investigated in explanted chick pineal glands at 4, 10 and 21 d of age. Nocturnal levels of the enzyme and the response of the enzyme to light exposure were determined in pineal glands maintained in short-term culture at each age. The results indicate that nocturnal NAT activity was increased in the glands from older birds. Nocturnal levels of NAT activity at the time of the initiation of the experiment were threefold greater in glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The half-time for light-induced inhibition of nocturnal enzyme activity in intact chick pineal glands is in agreement with previous studies from this laboratory (Rudeen et al, 1990), but is much slower than that observed in pineal glands from adult chickens (Binkley et al, 1975). Binkley et al (1975) demonstrated a half-time for light induced inhibition of NAT in adult birds exposed to light at the mid-point of the nocturnal regime to be approximately 10min.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The half-time for light-induced inhibition of nocturnal enzyme activity in intact chick pineal glands is in agreement with previous studies from this laboratory (Rudeen et al, 1990), but is much slower than that observed in pineal glands from adult chickens (Binkley et al, 1975). Binkley et al (1975) demonstrated a half-time for light induced inhibition of NAT in adult birds exposed to light at the mid-point of the nocturnal regime to be approximately 10min.…”
Section: Discussionsupporting
confidence: 91%
“…Animals were maintained under these conditions for three days before use. Previous studies indicate that NAT activity in explanted pineal glands from chicks at this age is sensitive to light inhibition (Rudeen et al, 1990). At the end of the acclimation period, each chick was decapitated, and the pineal gland was removed using aseptic techniques.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in rats, day-night differences in NAT gene expression in the pineal become apparent at postnatal day 5, shortly before rhythmical changes in NAT activity are detected (Pfeffer and Stehle, 1998). However, in birds, or at least in precocial birds, there is evidence for rhythmicity in pineal NAT mRNA (Herichová et al, 2001), NAT activity (Binkley and Geller, 1975;Herichová et al, 2001;Rudeen et al, 1990), and pineal melatonin content (Herichová et al, 2001;Zeman et al, 1992) before hatching. Interestingly, although chick embryos incubated on a long photoperiod show a rhythm in plasma melatonin, embryos on a short photoperiod do not, and have consistently low melatonin (Zeman et al, 1999).…”
mentioning
confidence: 99%